Pengaruh E-Wom, Layanan dan Literasi Keuangan Syariah Terhadap Loyalitas Nasabah Dengan Religiusitas Sebagai Variabel Moderasi - Mulyanti, Sri; Wulandari, Fitri (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to analyze the influence of the intensity of E-Word of Mouth (E-WOM) use, service quality and the level of Islamic financial literacy on customer loyalty mediated by religiosity owned by BSI KC Solo Slamet Riyadi 2 customers. Using a sample of 100 respondents, this study applies a purposive sampling technique, namely customers who are 18 years old, not priority customers, have been customers for more than one year. The data was processed using SmartPLS 4. The results of the study show that E-WOM, service quality have a direct effect on customer loyalty. The level of Islamic financial literacy doesn’t effect on influencing customer loyalty. Religiosity moderates the influence of e-WOM and service quality on customer loyalty, Religiosity does not moderate the influence of the level of Sharia financial literacy on customer loyalty. This study succeeded in proving the role of E-WOM, service quality and the level of Islamic financial literacy in influencing customer loyalty. Service quality tends to play the biggest role in influencing customer loyalty.